Native Language Teaching Problems and School Educational Reform - Maglakelidze, Natela ("Intercultural Dialogues" Transactions, 2025)
The article discusses the issues of Georgian language teaching in Georgian schools at the modern stage. Among the fields of linguistics, grammar issues are presented the most extensively in the national curriculum. This is natural, as the well-thought-out knowledge of grammar is the basis for the formation of proper spelling, punctuation and stylistic habits in students, which is ultimately aimed at improving their oral and written speech. Language classes at the basic level of school education must be given a separate academic hour. In fact, these will not be lessons of grammar, but of speech culture. But this does not mean at all that we should include material in the textbooks without taking into account the age characteristics of the student, overloading them with complex grammatical categories, which in many cases are disputed among linguists themselves; Let's endlessly confront the rules... What to teach and how to teach - this is one of the main and relevant issues in teaching the grammar of the Georgian language today.